2006
DOI: 10.1016/j.jtcvs.2006.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Acute type A aortic dissection complicated by stroke: Can immediate repair be performed safely?

Abstract: In our experience, surgical repair of acute type A aortic dissection can be performed in the setting of preoperative stroke with acceptable mortality. Moreover, no worsening of neurologic condition was observed after surgical repair. Immediate surgical repair is warranted even if acute type A aortic dissection is complicated by stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 13 publications
3
135
0
1
Order By: Relevance
“…Shortening the length of time between onset of cerebral symptoms and dissected aortic surgery was critical for improved outcomes in this subset of patients. Estrera et al [23] reported improved outcomes in AAAD patients who underwent cardiac surgeries within 10 h of neurological symptom onsets.…”
Section: [22]mentioning
confidence: 99%
“…Shortening the length of time between onset of cerebral symptoms and dissected aortic surgery was critical for improved outcomes in this subset of patients. Estrera et al [23] reported improved outcomes in AAAD patients who underwent cardiac surgeries within 10 h of neurological symptom onsets.…”
Section: [22]mentioning
confidence: 99%
“…Other investigators stated that neurologic findings may be reversible, and immediate surgery should not be contraindicated. 50,51) Broad cerebral infarction, however, may cause severe brain edema by cardiopulmonary bypass. In such cases, delayed surgery may be recommended.…”
Section: Cerebral Malperfusionmentioning
confidence: 99%
“…Moreover, some cases fully recovered by immediate surgery within 3 hour after ER arrival [5]. Our patient showed left hemiplegia perioperatively, which was not aggravated by immediate surgery, revealing minimal cerebral ischemic changes on MRI.…”
Section: Discussionmentioning
confidence: 53%
“…Emergency surgery in patients with those risk factors usually is avoided because of high mortality and morbidity. One reason, avoiding surgery, is that anticoagulant use during intraoperative extracorporeal circulation may promote hemorrhagic cerebral infarction or posttraumatic intracranial hemorrhage [5]. Regarding our patient, despite three preoperative poor prognostic factors, the recovery suggests that the effects of these factors remained minimal.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation